A survey on the anti-Trichomonas vaginalis effect of the hydroalcoholic extract of various medicinal plants in vitro - Mahnaz Jafari; Hossein Amini-khoei; Mohsen Cheshmpanam; Rahman Abdizadeh (Journal of Shahrekord University of Medical Sciences, 2023)
Background and aims: Trichomoniasis is the most common non-viral sexually transmitted infection worldwide; although it is treated by a 5-nitroimidazole drug family such as metronidazole (MTZ) with numerous side effects, and in this regard, alternative new drugs are required. Therefore, this study examined the anti-Trichomoniasis effect of the hydroalcoholic extract of some traditional medicinal plants of Iran in vitro. Methods: In this experimental study, the hydroalcoholic extracts of medicinal plants were prepared by maceration at a stock concentration of 20 mg/mL in the saline solution and then used for in vitro anti-trichomonas experiments. Trichomonas vaginalis trophozoites were isolated from the patient and cultured in a Trypticase Yeast extract Iron-Serum-33 medium. In addition, 200 μL of the culture medium containing 5×104 trophozoites was diluted in plate wells, and 10 doses were separately added on trophozoites for each extract serially diluted between 0.12 and 16 mg/mL in triplicate. The plates were incubated for 48 hours at 37 ° C with 5% CO2 . The number of trophozoites was counted with a hemocytometer and Trypan blue staining. Finally, the half maximal inhibitory concentration (IC50) was calculated by probit analysis. Results: Among the tested plants, Eugenia caryophyllata, Camellia sinensis, and Terminalia chebula Retz showed the best anti-trichomonal activity with IC50 values of 1.21, 1.62, and 1.66 mg/mL, respectively. All tested extracts had more IC50 than MTZ (IC50 100 mg/mL), an antiprotozoal drug used as a positive control. Conclusion: According to the results of this study, E. caryophylata, C. sinensis and T. chebula Retz affected the growth of T. vaginalis. Thus, it is recommended that other studies use this plant for the treatment of trichomoniasis infection.